What The Best Prediction Financial Distress With Compare Zmijewski, Altman Z-Score And Ohlson ? - DARMAYANTI, Novi; ASRORI, Muhammad; DAMAYANTI, Damayanti; RIKAH, Rikah; KUNTARDINA, Ari (Journal of Tourism Economics and Policy, 2023)
financial distressis a condition where the company's finances are experiencing a loss because it is considered unable to pay its obligations when they are due. The increase in cigarette excise rates will certainly have an impact on the shares of cigarette issuers and result in an increase in the selling price of cigarettes which will allow the company to experience financial distress. Cigarette companies need to analyze the company's financial condition, in which companies can predict opportunities for financial distress. Among them are using bankruptcy prediction models, one of which is zmijewski, altman z-score and ohlson. The aim of the researchers was to determine the prediction of financial distress in cigarette companies listed on the IDX for the 2018-2022 period using the Zmijewski method, altman z-score and Ohlson. This research is a descriptive research,The results show that the Zmijewski method predicts all healthy companies, the Altman Z-Score method for three companies is said to be healthy and the Ohlson method has two companies in good health. Ohlson's method has a high degree of accuracy72% with Typel Elrror 1 at 20% and Typel Elrror II at 8%. So that the Ohlson model is the most appropriate to use in predicting financial distress in cigarette companies listed on the Indonesian Efek Exchange (BEI).